Exploring diabesity pathophysiology through proteomic analysis using Caenorhabditis elegans - Subhadra, Malaimegu; Mir, Dilawar Ahmad; Ankita, Koley; Sindunathy, Muthukrishnan; Kishore, Hambram David; Ravichandiran, Velayutham; Balamurugan, Krishnaswamy (Frontiers in Endocrinology, 2024)
Introduction Diabesity, characterized by obesity-driven Type 2 diabetes mellitus (T2DM), arises from intricate genetic and environmental interplays that induce various metabolic disorders. The systemic lipid and glucose homeostasis is controlled by an intricate cross-talk of internal glucose/insulin and fatty acid molecules to maintain a steady state of internal environment. Methods In this study, Caenorhabditis elegans were maintained to achieve glucose concentrations resembling the hyperglycemic conditions in diabetic patients to delve into the mechanistic foundations of diabesity. Various assays were conducted to measure intracellular triglyceride levels, lifespan, pharyngeal pumping rate, oxidative stress indicators, locomotor behavior, and dopamine signaling. Proteomic analysis was also performed to identify differentially regulated proteins and dysregulated KEGG pathways, and microscopy and immunofluorescence staining were employed to assess collagen production and anatomical integrity. Results Worms raised on diets high in glucose and cholesterol exhibited notably increased intracellular triglyceride levels, a decrease in both mean and maximum lifespan, and reduced pharyngeal pumping. The diabesity condition induced oxidative stress, evident from heightened ROS levels and distinct FT-IR spectroscopy patterns revealing lipid and protein alterations. Furthermore, impaired dopamine signaling and diminished locomotors behavior in diabesity-afflicted worms correlated with reduced motility. Through proteomic analysis, differentially regulated proteins encompassing dysregulated KEGG pathways included insulin signaling, Alzheimer’s disease, and nicotinic acetylcholine receptor signaling pathways were observed. Moreover, diabesity led to decreased collagen production, resulting in anatomical disruptions validated through microscopy and immunofluorescence staining. Discussion This underscores the impact of diabesity on cellular components and structural integrity in C. elegans, providing insights into diabesity-associated mechanisms.